Niematerialne źródła tworzenia wartości w przedsiębiorstwie - analiza pojęć - Urbanek, Grzegorz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The growing part of company value is created by intangibles. In connection with intangibles we witness in literature a several debates. This paper joins the debate on definitions of intangible sources of company value. In subject literature, we can find many related concepts, such as intangible assets, intellectual capital, intellectual property, competences, abilities, intangible resources etc. In general, these concepts are used in different contexts to describe intangible, non-monetary various sources of probable future economic benefits for their owner. This paper proposes definitions setting in order notions related to intangible sources of company value and presents their interrelations. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 578-587